Satisfaction as Effect Mediation of Brand Image and Customer Relationship Management on Customer’s Loyalty - Ferdiawan, Y; Hermawan, A; Wardana, L W; Arief, M; ., Sarbini (KnE Social Sciences, 2018)
This study aims to determine the effect of brand image and customer relationship management on customers’ loyalty directly or through customer satisfaction. This study uses a quantitative research design and sampling technique by using purposive sampling. The population in this study are all customers of a Bank in Malang that consists of 200,000 customers with a total sample of 100 customers. Data analysis was done by using path analysis with SPSS 16.0. The results of this study are: (1) brand image has significant positive effect on customer satisfaction, (2) customer relationship management has significant positive effect of customer satisfaction, (3) brand image has positively significant effect on customer loyalty, (4) customer relationship management has significant positive effect on customer loyalty, (5) customer satisfaction has significant positive effect on customer loyalty, (6) brand image has indirect significant positive effect on the customer loyalty through customer satisfaction, and (7) customer relationship management has indirect significant positive effect on the customer loyalty through customer satisfaction. Keywords: Brand Image, Customer Relationship Management, Customer Satisfaction, Customer Loyalty